Locusts: Red Alert - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
As predicted, the rains that have returned to the Sahel have also brought on a locust infestation. Mali and Burkina Faso have been the first countries to be affected and farmers have had to re-sow their crops. Senegal and Mauritania are expected to...